PENGARUH KUALITAS PRODUK, EKUITAS MEREK, PERSEPSI HARGA TERHADAP PEMBELIAN ULANG PADA PELANGGAN MOTOR YAMAHA DI KABUPATEN KENDAL - Prameswara, Agtika; Euis Soliha (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of Product Quality, Brand Equity and Price Perception on Repurchase of Yamaha motorcycles in Kendal district. This research was conducted throughout the Kendal district. The analytical tool used is multiple regression, as for testing the hypothesis that is using the t test. Collecting data through a questionnaire with measurements using a Likert scale of 1-5 for alternative answer points. This sampling method is purposive sampling and the number of samples in this study is 100 respondents. The results showed that Product Quality had a positive and significant effect on Repurchase, Price Perception had a positive and significant effect on Repurchase, but Brand Equity had no positive and significant effect on Repurchase.